2023
DOI: 10.3390/app132212267
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Optimization of EOR Screening by Implementing Machine Learning Algorithms

Shengshuai Su,
Na Zhang,
Peng Wang
et al.

Abstract: Enhanced oil recovery (EOR) is a complex process which has high investment cost and involves multiple disciplines including reservoir engineering, chemical engineering, geological engineering, etc. Finding the most suitable EOR technique for the candidate reservoir is time consuming and critical for reservoir engineers. The objective of this research is to propose a new methodology to assist engineers to make fast and scientific decisions on the EOR selection process by implementing machine learning algorithms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…They found that the RF performed the best with an accuracy of 0.91. Su et al 18 used the RF, ANN, NB, SVM, and DT for EOR screening of 13 EOR techniques as a function of porosity, permeability, depth, gravity, temperature, viscosity, net thickness, and initial oil saturation. They used 956 EOR experiences to train, validate, and test their models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that the RF performed the best with an accuracy of 0.91. Su et al 18 used the RF, ANN, NB, SVM, and DT for EOR screening of 13 EOR techniques as a function of porosity, permeability, depth, gravity, temperature, viscosity, net thickness, and initial oil saturation. They used 956 EOR experiences to train, validate, and test their models.…”
Section: Literature Reviewmentioning
confidence: 99%